Narratives in Javanese Farmer Batik - Bani Sudardi (Javanologi: International Journal of Javanese Studies, 2023)
When batik grows in a rural environment, the batik is also colored by the values that exist in rural areas. Batik is never out of the nuances of the wearer. Although cursory the same, batik outside the palace still voiced his own dreams and hopes. Batik palace voiced legitimacy and power. Batik outside the palace, especially batik called as farmer's batik. Therefore, farmers' batik represents its own voice from the structure of Javanese society. There are any new narratives in the Javanese farmer batik. This research uses descriptive method. The subject of the study was described to find the value of ideologies’ and narrative in farmer's batik. Data sources include artifact, social facts, and interview results. It was then processed to get the perfect description. The farmer's batik expresses the hope of a glorious life. Therefore, although there is sido mukti batik, but sidomulya more popular in the countryside because of these expectations. The atmosphere of the forest gave rise to a motif of reason-the reason for the voices of the wooded countryside. The forest is a symbol of complete perfection of self-sufficient life. Batik farmers raised by removing the ban pattern so that there is no collision with batik kraton. Batik farmers are batik rural people who want to live peacefully with nature and the environment. Inside were typical village scenery like rice, algae, rustic plants, small birds, butterflies, and others. Often also raised snakes in the form of bonfires called "buketan naga wisikan" bouquet of dragons that are talking. Narrative contained in peasant batik is not a complete narrative. The message conveyed is a message of peace. A peaceful rural atmosphere is reflected in the emerging motives. This is in keeping with the cool rural conditions of peace and still many animals adorn life.